Le Rapport de l'Office de revision du Code civil sur la personnalité juridique - Deleury, Edith; Demers, Robert (Les Cahiers de droit, 1977)
The Civil Code Revision Office has produced an interesting report on legal personality. In this commentary, the authors have sought to underline the major changes suggested by the Report and to criticize certain positions adopted therein. The major areas of controversy, such as the respect of privacy, the rights of children and the nature of corporations as fictitious persons have been examined in some detail. On the whole, the Report produces a fine compendium of the existing rules whilst suggesting changes that reveal a conscience of the urgent problems on the question.